2007
DOI: 10.1007/s00213-007-0916-7
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of serotonin2C receptors influences cocaine-seeking behavior in response to drug-associated stimuli in rats

Abstract: These findings, provided they can be extrapolated to abstinent human addicts, suggest therapeutic potential for the selective 5-HT2C agonist in preventing cue-controlled cocaine-seeking and relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 90 publications
(117 reference statements)
7
43
1
Order By: Relevance
“…We subsequently found that Ro60-0175 reduced reinstatement of cocaine-seeking behavior induced by priming injections of cocaine, by a pharmacological stressor, yohimbine, and by contextual cues previously associated with self-administered cocaine [31,43]. These findings have been replicated and extended by several other groups using a variety of reinstatement procedures and 5-HT 2C receptor agonists [44][45][46]. To the extent that reinstatement procedures model processes involved in relapse [47], these data suggest a broad role for 5-HT 2C agonists in the treatment of drug abuse and addiction.…”
Section: Reviewmentioning
confidence: 78%
“…We subsequently found that Ro60-0175 reduced reinstatement of cocaine-seeking behavior induced by priming injections of cocaine, by a pharmacological stressor, yohimbine, and by contextual cues previously associated with self-administered cocaine [31,43]. These findings have been replicated and extended by several other groups using a variety of reinstatement procedures and 5-HT 2C receptor agonists [44][45][46]. To the extent that reinstatement procedures model processes involved in relapse [47], these data suggest a broad role for 5-HT 2C agonists in the treatment of drug abuse and addiction.…”
Section: Reviewmentioning
confidence: 78%
“…Furthermore, the functional role of central 5-HT 2C Rs in the effects of cocaine was assessed using the 5-HT 2C R agonist Ro 60-0175, administered at a dose (1 mg/kg) known to selectively target central 5-HT 2C Rs Di Matteo et al, 2004) and modulate cocaine-induced effects (Grottick et al, 2000;Burbassi and Cervo, 2008;Fletcher et al, 2008;Cathala et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The dose of cocaine was selected on the basis of previous studies reporting its ability to increase DA-dependent behaviors, as well as in vivo DA release and Fos expression in the rat striatum (Grottick et al, 2000;Navailles et al, 2004;Young et al, 1991). Dose and pretreatment administration time of Ro 60-0175 were chosen according to previous studies reporting its efficacy to modulate cocaine-induced behavioral effects through selective stimulation of central 5-HT 2C Rs (Grottick et al, 2000;Burbassi and Cervo, 2008;Fletcher et al, 2008). Dose and pretreatment administration time of SB 242084 were chosen according to previous studies reporting its efficacy to block the effect of Ro 60-0175 on cocaineinduced behavioral and molecular responses (Grottick et al, 2000;Fletcher et al, 2008;Cathala et al, 2014).…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…This suggestion should be confirmed in future studies on the effect of site-specific injections of mu-opiate receptor antagonists on context-induced reinstatement. Systemic injections of Ro 60-0175 (an agonist of 5-HT 2C serotonin receptors) or SR141716A (an antagonist of cannabinoid receptor 1, CB1) decrease drug priming-and discrete cue-induced reinstatement of drug seeking (Grottick et al 2000;De Vries et al 2001, 2003Burbassi & Cervo 2008). Based on these studies, Fletcher et al (2008) examined the effect of systemic injections of Ro 60-0175 on context-induced reinstatement of cocaine seeking, and Diergaarde et al (in press) examined the effect of systemic injections of SR141716A on context-induced reinstatement of nicotine seeking.…”
Section: Pharmacology and Neuroanatomy Of Context-induced Reinstatementmentioning
confidence: 99%